Possibilities of Future Double Beta Decay Experiments to Investigate Inverted and Normal Ordering Region of Neutrino Mass - Barabash, Alexander S. (Frontiers in Physics, 2019)
An overview of modern experiments on the search for neutrinoless double decay is presented. The obtained limits on the effective mass of the Majorana neutrino m_ν are discussed taking into account the uncertainties in the value of the nuclear matrix elements (NMEs) and the value of the axial-vector constant g_A. Predictions for the values of the m_ν from the results of oscillation experiments and modern cosmological data are presented. The possibilities of the next generation experiments with sensitivity to m_ν at the level of 10-50 meV (studying mainly the inverted ordering (IO) region) are discussed. %Description of the most developed and promising projects is presented. The prospects for studying the normal ordering (NO) region are discussed too. It is shown that the possibilities of studying the NO depend on the mass of the lightest neutrino m_0. In the limiting case of small mass (m_0 0.1 meV), the values of m_ν ≈ 1-4 meV are predicted, which makes the study of this region inaccessible by the next generation experiments. But there is an allowed region of m_0 (7-30 meV) in the framework of NO, where the predicted values for m_ν could be 10-30 meV and that is quite achievable for the next generation experiments. The possibility to rich in the future sensitivity to m_ν at the level of 1-10 meV is also discussed.